Keterampilan Psikomotor Fisika Siswa Melalui Model Pembeajaran Kooperatif Tipe Number Head Together - Azizahwati Azizahwati; Librina Eka Puteri; Hendar Sudrajad (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2010)
This study is aimed at describing psichomotor skill of senior high school student of SMA N 12 Pekanbaru.This study used the Number head together of cooperative learning model. The data collected by psychomotorskill test. The average absorbtion of student is low, the completeness of material is very high and theclassical completeness of student is high.